Prevalence of Low Back Pain and its Impact on Quality of Life among Taif University Students - Ahmad, Ayman Abdelbaky; Althobaiti, Turki Abdulmuin; Alsofiany, Mohammed Saleem; Altowairqi, Moayad Abed; Aljuaid, Omar Eid; Althobaiti, Muhammad Abdullah; Alamri, Faris Mohammed (International Journal of Innovative Research in Medical Science, 2021)
Background: Lower back pain (LBP) is associated with increased pain intensity, physical and psychological disability, and increased dependence on pain medications causing adverse effects on the day-to-day quality of life (QOL). The study aimed to assess the prevalence of LBP among Taif University students and its impact on quality of life. Methods: A pretested self-administered questionnaire was distributed randomly and electronically to all students who gave consent to participated. The questionnaire was be divided into three parts. The first part included demographic details; the second part assessed the prevalence of Low back pain and associated data that was recorded using the LBP section of Standardized Nordic Musculoskeletal Questionnaire (SNMA); the third part consisted of the RAND 36-Item Short-Form Health Survey (SF-36) for assessing the quality of life. Result: In our study majority of the participants were females (87.3%), and 55.3% belonged to the 20-25 years age group. The fixed orthodontic related history showed 59.8% had undergone the treatment for 1 to 3 years and 31.6% of the participants reported that they had removed the fixed braces for more than five years. Among these participants, 89.5% (n=34) reported that the fascia (space) closed between the upper frontal teeth after Frenectomy, and 65.8% (n=25) agreed that spaced between the two upper front teeth still closed after removing the retainer. Conclusion: The lifetime prevalence, annual prevalence, and point prevalence of LBP were found to be 57.9%, 73.1%, and 47.1%, respectively. The point prevalence was statistically higher among female students than male students (p=0.003). There were statistically significant differences seen in lifetime and point prevalence of LBP between different colleges. A linear regression model showed that the annual prevalence of LBP had a significant impact on the students' quality of life.